Cold eternity - Barnes, S. A. (Tor Publishing Group, 2025)
"Halley is on the run from an interplanetary political scandal that has put a huge target on her back. She heads for what seems like the perfect place to lay low: a gigantic space barge storing the cryogenically frozen bodies of Earth's most fortunate citizens from more than a century ago... The cryo program, created by trillionaire tech genius Zale Winfeld, is long defunct, and the AI hologram "hosts," ghoulishly created in the likeness of Winfeld's three adult children, are glitchy. The ship feels like a crypt, and the isolation getsto Halley almost immediately. She starts to see figures crawling inthe hallways, and there's a constant scraping, slithering, and rattling echoing in the vents. It's not long before Halley realizes she may have gotten herself trapped in an even more dangerous situation than the one she was running from..."--Provided by publisher.